The Canada Council Collection. (Ottawa : National Gallery of Canada, 1969)
Barbeau, Marcel ; Bloore, Ron ; Breeze, Claude ; Curnoe, Greg ; Goguen, Jean ; Comtois, Ulysse ; Hurtubise, Jacques ; Gagnon, Charles ; Martin, Ron ; Kiyooka, Roy ; Molinari, Guido ; Lochhead, Kenneth ; Morris, Michael ; N.E. Thing Co ; Onley, Toni ; Snow, Michael ; Tousignant, Claude ; etc.
The Canada Council Collection / La collection du Conseil des Arts du Canada. A travelling exhibition of the National Gallery of Canada, Ottawa, 1969 / Une exposition itinérante de la Galerie nationale du Canada, Ottawa, 1969
boek